MATHEMATICS MODEL OF COMPACT TUMOR TO ANALYZE THE EFFECT ANTIANGIOGENIC THERAPY - Arfi, Eristia; Putri, Dwi Mutiara; Wibarani, Yeni Gede; Rizka, Nela (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2024)
Based on their growth, tumors are classified into benign(compact) tumors and malignant (invasive) tumors. One of the treatments used for tumors is antiangiogenic therapy because this therapy has low toxicity. This study examines the effect of antiangiogenic therapy on compact tumors. The number of tumor cells changes over time are influenced by proliferation, death, and migration tumor cell. Antiangiogenic therapy can inhibit the process of angiogenesis which affect the dynamics of glucose flow. A lack of glucose flow will cause a decrease in tumor cell proliferation process which will decrease tumor growth rate. The finding suggests that maintaining glucose levels at or below a critical threshold is effective therapy.